When is mental toughness needed in judo? Perceptions of athletes and coaches with different levels of achievement - Silva, V.; Dias, C.; Corte-Real, N.; Fonseca, A. M. (Revista Portuguesa de Ciências do Desporto, 2017)
Considering the lack of research focused on the circumstances that require mental toughness in judo, this study`s purpose was to explore the perceptions of those demanding situations between athletes and coaches. Nine coaches and 12 athletes, with different levels of achievement, were interviewed. Semi-structured interviews applied the "experience" corollary of the personal construct psychology theory. Interview transcripts were subjected to inductive content analysis. The resulting conceptual framework that arose from raw data revealed 25 mentally demanding situations in judo. Five were exclusively reported by coaches: death, parents and family, personal problems, logistics and club changing. Golden score was merely identified by athletes. Only one situation was reported among all 21 participants: results in competition. Considering the scarce available literature, four situations identified were suggested to be peculiar to judo: weight loss, unpredictability in judo fight, nature of judo fight and golden score. Additionally, rivalries were suggested to be a reality particular to the sport`s elite.